Proximate Analysis and Chemical Constituents of Psychotria latistipula Benth. (Rubiaceae) Leaves - Samuel Akinniyi Odewo; Olayombo Margaret Banwo (Biology, Medicine, & Natural Product Chemistry, 2025)
Psychotria latistipula Benth. (Rubiaceae), a traditional Nigerian medicinal plant recognised for its effectiveness in treating cancer, tumours, bronchial and gastrointestinal disorders was investigated for its chemical constituents by Gas Chromatography-Mass Spectrometry (GC-MS) technique; also, proximate analysis was done to determine the composition of moisture, crude protein, crude fiber, fat, carbohydrate, and ash contents, which had not been previously reported. P. latistipula leaves were extracted by maceration using acetone and hexane (1:1). The proximate analysis indicated that the leaves of P. latistipula contain moisture, crude protein, crude fiber, fat, carbohydrate, and ash contents of 8.91±0.14, 12.43±0.05, 20.78±0.66, 2.28±0.06, 50.34±0.79, and 5.27±0.16%, respectively, demonstrating a notably high carbohydrate content. The GC-MS identified twenty-eight compounds, making up 93.08% of the total. The dominant classes of these compounds included fatty acid esters, saturated fatty acids, fatty acid methyl esters, and unsaturated fatty acid aldehydes accounting for 19.27%, 18.71%, 13.77% and 13.36% of the total, respectively. Octadecanoic acid (14.03%) was the major compound in P. latistipula leaves acetone-hexane extract. Notably, Octadecanoic acid is known for its potential anti-inflammatory, anticancer and antioxidant properties, which indicates P. latistipula could serve as an anti-inflammatory, antioxidant and anticancer agents further justifying its ethnomedicinal use.